EXPLORING ENABLERS, BARRIERS AND OPPORTUNITIES TO DIGITAL SUPPLY CHAIN MANAGEMENT IN VIETNAMESE MANUFACTURING SMES - Nguyen Phuc Khanh Linh; Vikas Kumar; Ximing Ruan (International Journal of Organizational Business Excellence, 2019)
This paper examines the enablers, barriers and opportunities of digital supply chain management (DSCM) in manufacturing Small and Medium-sized Enterprises (SMEs) in Vietnam fromexpert’s perspective. The study is a foundational effort to contribute to the establishment of new digital management era in many emerging economies. Applying a systematic literature review (SLR) of relevant studies and a qualitative data methodology this research also aims to explore the factors affecting technology adoption in supplychain management from managerial perspective of Vietnamese manufacturing SMEs. Findings of the research reveal that the enablers and barriers are classified into four main dimensions which are Organisational, Technological, Strategic and Legal –Ethical issues. In addition, our findings also reveal that external factors deeply influence the adoption intention in Vietnamese manufacturing SMEs. The development of digital SCM could be different in each case according to companies’ characteristics and business environment. Our study therefore adds to the limited research in the domain of digital technology adoption in SMEs in developing country context.